Financial innovation and economic growth in Bangladesh - Md. Qamruzzaman; Wei Jianguo (Financial Innovation, 2017)
Background: This study provides evidence for the financial innovation in the financial system that resulted in the economic growth of Bangladesh from 1980-2016. Methods: To capture the influence of financial innovation on economic growth, we estimated the long-run cointegration by applying Autoregressive Distributed Lag (ARDL) bound testing and Granger causality-based Error Correction Model (ECM) to capture the directional association. Results: The Test of Cointegration satisfied the existence of a long-run association between economic growth and the financial innovation proxies, which were the Domestic Credit to the Private Sector (DCB) as a percentage of the Gross Domestic Product and the Broad-to-Narrow Money (M2/M1) as a percentage of the Gross Domestic Product. Our results showed that in the long run, credit circulation to the private sector and monetary management play important roles in economic growth. We also found that the coefficients of the financial innovation proxy variables were positive and statistically significant both in the short run and long run. We also ran Granger causality tests to investigate the directional effect. This study confirmed the feedback causality between the economic growth and 2 proxies of financial innovation in the short and long run. The gross capital formation and trade openness contribute significantly to explaining the economic growth in Bangladesh. Conclusion: The government of Bangladesh should encourage financial innovation in the financial system, especially at financial institutions, so that access to financial services can easily provide for equitable development. The government should also encourage financial innovation in the capital market, which will assist in raising long-term capital for investment and expedite overall economic growth.
Keywords: O3; O4; O53; 650; Financial innovation; Economic growth; ARDL; Granger causality